Sustained expression of inflammatory monocytes and activated T cells in COVID‐19 patients and recovered convalescent plasma donors - Ravinder Singh; Hamed Hemati; Meenu Bajpai; Pushpa Yadav; Ashish Maheshwari; Suresh Kumar; Sonal Agrawal; Jayesh Kumar Sevak; Mojahidul Islam; Jaswinder Singh Mars; Shiv K Sarin; Nirupama Trehanpati (Immunity, Inflammation and Disease)
Abstract Introduction Intense monocyte activation and infiltration into the target tissues are the main mechanisms of lung injury in severe acute respiratory syndrome coronavirus 2 infection. A reduction in the degree and nature of such cellular responses is expected following recovery. We aimed to investigate the immune responses in moderate coronavirus disease 2019 (COVID‐19) patients and recovered patients. Methods Moderate COVID‐19 patients (n = 34) at Lok Nayak Hospital, New Delhi, and COVID‐19 recovered patients (n = 15) from the mild disease who were considered for convalescent plasma (COPLA) donation at the Institute of Liver and Biliary Sciences, New Delhi and healthy individuals (n = 10), were recruited. We have assessed 21 plasma cytokines using cytokine bead array, performed proteomics on serum proteins, and analyzed immune cells using a detailed multicolor flow cytometry. Results A significant increase in inflammatory markers such as macrophage inflammatory protein (MIP)1‐α, monocyte chemotactic protein‐1, macrophage migration inhibitory factor, vascular endothelial growth factor‐A, and Leptin was observed in the moderate patients. Nonsurvivors additionally showed increased interleukin (IL)‐6 levels. Consistently, the proteomics analysis showed the signatures of cytokine production and interferon‐γ response, and increased level of acute‐phase protein SAA1 in the serum of COVID‐19 patients. Despite the sustained expression of MIPs, the recovered COPLA donors showed a surge in MCSF and IL‐18 levels. Both the groups had increased CCR2, CX3CR1 positive monocytes, low CD8+ T cells, A proliferation‐inducing ligand, and B‐cell activating factor receptor+ B cells compared with healthy subjects. Conclusions Patients who have recovered and considered for COPLA donations still have compromised immunity with sustained expression of inflammatory monocytes and activated T cells.